Efektivitas Terapi Hinosis Lima Jari Terhadap Ansietas Klien Hipertensi Di Puskesmas Rawasari Kota Jambi Tahun 2017 - Mohd Syukri (Universitas Batanghari Jambi, 2019)
Five-finger hypnosis is a movement that tightens and relaxes the muscles in one part of the body at one time which can present a relaxed condition physically and psychologically, by thinking of a pleasant experience (Keliat, 2011). Useful for giving inner peace to individuals. reduce anxiety, worry and anxiety, reduce tension and reduce blood pressure, lower heart rate and sleep soundly. This study aims to determine the effectiveness of five-finger hypnosis therapy against anxiety hypertension clients at Putri Ayu Health Center, Jambi City. Quasi experimental design pre-post test with without control. The sample was 33 people with a total sampling technique. The results showed that there was an effect of five-finger hypnosis therapy on anxiety in hypertensive clients (p value <0.05). There was a decrease in anxiety after five finger hypnosis therapy was carried out. Five finger hypnosis therapy is recommended to be applied as nursing therapy in treating hypertensive clients with anxiety.